Associations of depression and depressive symptoms with preeclampsia: results from a Peruvian case-control study - Garcia Pedro; Lam Nelly; Sanchez Sixto E; Qiu Chunfang; Williams Michelle A (BMC, 2007)
Abstract Background Preeclampsia involves endothelial dysfunction, platelet dysfunction/activation and sympathetic over-activity similar to cardiovascular disorders (CVD). Depression, an independent risk factor for progression of CVD, was found to be associated with an increased risk of preeclampsia among Finnish women. We examined the relation between depression/depressive symptoms and preeclampsia risk among Peruvian women. Methods The study included 339 preeclamptic cases and 337 normotensive controls. Depression and depressive symptoms during pregnancy were assessed using the Patient Health Questionnaire (PHQ-9). Odds ratios (OR) and 95% confidence intervals (CI) were estimated from logistic regression models. Results The prevalence of moderate depression was 11.5% among cases and 5.3% among controls. The corresponding figures for moderate-severe depression were 3.5% for cases and 2.1% for controls. Compared with non-depressed women, those with moderate depression had a 2.3-fold increased risk of preeclampsia (95% CI: 1.2-4.4), while moderate-severe depression was associated with a 3.2-fold (95% CI: 1.1-9.6) increased risk of preeclampsia. Associations of each of the 9-items of the PHQ-9 depression screening module with preeclampsia risk were also observed. Conclusion Our findings are consistent with the only other published report on this topic. Collectively, available data support recent calls for expanded efforts to study and address depression among pregnant women.